The Job search intention in the tourism, food and hospitality sectors: a systematic narrative review according to the PRISMA guidelines - Salazar-Duque, Diego; Llugsha Guijarro, Víctor; Larrea-Paredes, María de Lourdes (International Journal of Studies in Administrative Sciences STRATEGOS, 2026)
This narrative systematic review, conducted under PRISMA 2020 and the PARSIFAL protocol, analyzed empirical evidence on factors influencing job search intention (JPI) in the tourism, food service, and hospitality sectors. Open access empirical studies published between 2010 and 2025 in Spanish, English, or Portuguese, with qualitative, quantitative, or mixed-methods approaches that explicitly addressed JPI, were included. Grey literature, non-work-related studies, and low-quality studies were excluded. A search of Scopus and SpringerLink (up to August 1, 2025) identified three studies (n = 3). The first study showed that an external locus of control moderates the effect of parental support and professional practices on JPI. The second demonstrated that person-organization fit indirectly influences JPI through employer attractiveness. The third determined that compensation is the strongest predictor, followed by work-life balance and professional development. The synthesis grouped the findings into psychological, organizational, and labor dimensions. The main limitations were methodological heterogeneity and limited geographical diversity. The results highlight the importance of individual and structural factors in strengthening employability policies and talent management.